Fast Fault-Tolerant Grid Frequency Measurement - Chris Wembridge; Mark Davies; James Lord; Evan Franklin; Sarah Lyden; Michael Negnevitsky (IEEE Open Access Journal of Power and Energy)
As power systems adopt greater levels of asynchronous generation, operators increasingly need to accurately monitor and manage their systems. With inverter-based generation progressively displacing traditional synchronous generators, power systems generally experience increased rate of change of grid frequency and wider propagation of voltage disturbances after a network contingency event. Inverter-based resources are now being leveraged to mitigate larger frequency disturbances, by delivering fast frequency control ancillary services. For this to be effective, accurate and robust, fast and fault-tolerant grid frequency measurements are needed. Commonly deployed frequency measurement techniques are susceptible to significant measurement error when exposed to unbalanced faults and frequency deviations. More robust techniques for measuring frequency are thus needed. This paper describes in detail a measurement strategy that extracts the continuous phase angle of the positive phase sequence phasor, from voltage signals. The method is demonstrated to provide robust measurements in the presence of simultaneously and rapidly varying voltage and frequency. From real-world measurements, using the Tasmanian power system as a case-study, the method is shown to be equivalent to or outperform measurement devices currently deployed in power systems. This paper provides all necessary control block diagrams required for integration into various modelling packages and frequency measurement devices.